Mucin secretion activity of gastric cancer as a prognostic factor: a clinicopathological analysis - Huszno, Joanna; Mrochen-Domin, Izolda; Zembala-Nożyńska, Ewa; Tukiendorf, Andrzej; Lange, Dariusz; Nowara, Elżbieta (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : Gastric cancer is characterized by varying secretion of mucus. Mucin producing gastric carcinoma (MUC) is thought to be a histological subtype with a worse prognosis. The aim of this study was to compare the clinicopathological differences between MUC and other types of gastric carcinoma without secretion of mucus (NMUC). Material and methods : We reviewed two groups of patients with pathologically confirmed gastric cancer: 34 patients with MUC and 36 cases with NMUC. Patients’ sex, age, tumor location, stage of disease and type in the Lauren classification were examined. We analyzed the presence of lymph node metastasis, peritoneal dissemination and liver metastasis. Additionally, treatment response, toxicity and survival rates were evaluated. Results : We observed a statistically significant relationship between MUC subtype and patients’ sex: MUC was found mostly in women (p = 0.017). There were no significant differences between the two gastric cancer groups according to age, tumor location, size of tumor or stage of disease. In the NMUC group the rate of liver metastasis was significantly higher (p = 0.001). The overall survival rate and progression-free survival for MUC patients were lower than those for NMUC patients. There was no significant difference in survival rates between the two groups. In analysis of logistic regression we distinguished significantly advantageous (number of chemotherapy cycles) and disadvantageous parameters (advanced stage in TNM), which influenced the chemotherapy effect. Conclusions : The MUC type itself is not an unequivocally negative prognostic agent. Poor prognosis was correlated with more advanced stages at diagnosis, particularly with dissemination of cancer.